Perlindungan Hukum Bagi Nasabah dalam Perjanjian Kredit Bank - Hasan, Kusman; Moonti, Roy Marthen (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Bank credit agreements are often drafted in the form of standardized clauses that are detrimental to customers because they are made unilaterally by banks without room for negotiation. This position imbalance is exacerbated by low legal literacy and information asymmetry between the two parties. This research aims to analyze the ideal form of legal protection for customers in the face of harmful standard clauses. Through a normative juridical approach and case studies, it is found that regulations such as the Consumer Protection Law and POJK have provided a legal basis, but their implementation is still weak. Ideal legal protection includes three aspects: preventive, repressive, and curative, and requires the active role of the state and OJK as supervisors. Regulatory updates, strengthened legal education, and fairer contract supervision are needed to create an equitable and inclusive financial ecosystem. Effective protection will also strengthen public confidence in the banking sector.